DOES OFFICE BLOOD PRESSURE STILL RELIABLE IN TYPE 2 DIABETES MELLITUS TO ASSESS BLOOD PRESSURE CONTROL?. (April 2021) - Allouche, Emna; Ahmed, Habib Ben; Abid, Omar; Boudiche, Faten; Beji, Mohamed; Ouechtati, Wejdene; Bezdah, Leila
Abstract : Objective: Ambulatory blood pressure (ABP) monitoring in type 2 diabetes (T2DM) is not yet routine in clinical practice. We aimed to quantify abnormal ABP patterns and their associations with diabetic complications and to assess the reliability of office blood pressure (OBP) for assessing BP control in T2DM. Design and method: In a cross-sectional study, eligible patients with T2DM underwent OBP and 24- hour ABP measurements under standardized conditions and screening for diabetic complications. Results: Eighty patients (mean age 58 + 10 years, males 30%) completed assessment. All patients had a known history of hypertension. Non-dipping and nocturnal systolic hypertension (SHT) were prevalent in 54 (67, 5%) and 30(37, 5%) patients, respectively. Non-dipping had a significant association with microvascular complications (p = 0, 001). There was no association between other abnormal ABP patterns and diabetic complications. The sensitivity and specificity of OBP for assessing BP control were 52% and 63% respectively. The positive and negative predictive values were 31% and 81% respectively. Conclusions: Non-dipping, reverse dipping and nocturnal SHT are highly prevalent in patients with T2DM with a known history of hypertension. Compared with nocturnal SHT, non-dipping may be a stronger predictor of end-organ damage. The reliability of OBP for assessing BP in T2DM is only modest. Patients with T2DM are likely to benefit from routine ABP monitoring.